S M A Rashidul Hasan - Hasan, Md. Mahmudul (Asiatic Society of Bangladesh, 2011)
S M A Rashidul Hasan (1932-1971) had his early education at the historic Bhabta Azizia Madrasah in the district of Murshidabad in India. In 1947 he completed his secondary education from the same Madrasah. At that time his elder brother Toyob Ali was the first secretary to the British High Commissioner in Dhaka, so Rashidul Hasan then moved to Dhaka to continue his education under his guardianship. In 1949 he completed his IA (Intermediate in Arts) degree from Dhaka Islamia Intermediate College. He then took admission at Dhaka University and completed his BA (Honours) and MA in English literature in 1952 and 1954 respectively. But circumstances did not allow him to stay in his birthplace, West Bengal. In order to regain his Indian citizenship, he surrendered his Pakistani passport – which he happened to have because of his stayal in East Pakistan after the partition of 1947 – to the government of West Bengal. For a long period of eight years, Rashidul Hasan relentlessly tried to regain his Indian nationality and went from door to door in government offices, but on different excuses West Bengal government delayed and finally rejected his application. Frustrated and utterly betrayed, in 1967 he resolved to come back to Dhaka and his wife complied. Rashidul Hasan’s second spate of sufferings began in 1971; but this time it took a vicious turn and ended his life. He was killed by the Pakistani army during the conflict that gave birth to Bangladesh. Thus the life of Rashidul Hasan bears the brunt of the two major political upheavals of the region: the partition of 1947 and Bangladesh’s war of independence in 1971.